If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4-(3-1)2=0
We simplify the equation to the form, which is simple to understand
4-(3-1)2=0
Simplifying terms in parentheses
4-(+2)*2=0
Reorder the terms in parentheses
4-(+4)=0
Remove unnecessary parentheses
4-4=0
We move all terms containing to the left and all other terms to the right.
0=0-4+4
We simplify left and right side of the equation.
0=0
0=0
This equation is an identity, so all real numbers are solutions.
| x^2-2x^2-3x=0 | | w+9+3w=8+10w | | f(x)=x^3-2x^2-3x | | (3x)/(x^2+4x+3)+2/(x^2-1)=(4x)/(x^2+2-3) | | v^2+14v+40=0 | | -x^2-10x+144=0 | | s^2+8s=9 | | 4m^2-21m+27=0 | | 7u^2-19=324 | | 10x+570=5620 | | 10(5)+570=y | | 1/9(4t-4)=t+4/18 | | 9x-(3x+5)=3x-23 | | 18/3+2*6+7 | | 1/8(8t-5)=t+5/16 | | 10(2)+570=y | | 10(0)+570=y | | 4b-7=-14 | | 2x^2+3=4x+7 | | 2*5-6+21/3 | | 8y+0.04(y+2000)=1840 | | c=10h+20 | | 3+4*6-14/2 | | 4.5(1)+4=y | | 3a+4=5 | | 7log(4x+1)=11 | | 4.5(0)+4=y | | 2x-3=20/x | | 6(1)-2y=12 | | -.3(x-4)+x=.5(3-x) | | -1/2(0)-3=y | | 10x-1=-21 |